IMPROVEMENT OF PRODUCTION PERFORMANCE OF SOFT-SHELL CRAB CULTURE THROUGH DIETARY SUPPLEMENTATION OF HIGH DOSE OF PURSLANE IN RECIRCULATING AQUACULTURE SYSTEM USING APARTMENT BOX - Effendi, Irzal; Putri, Risma Amelia; Wahjuningrum, Dinamella; Mulya, Muhammad Arif; Ansani Takwin, Bagus; Citarasu, Thavasimuthu (Politeknik Kelautan dan Perikanan Jembrana, 2026)
The major constraints in soft-shell crab (Scylla serrata) culture are the irregular and low frequency of molting, which reduce production efficiency. Previous studies have shown that purslane (Portulaca oleracea) supplementation significantly improves molting and production performance of soft-shell crab cultured in an apartment box using a recirculating aquaculture system; however, evaluations at higher doses remain limited. This study aimed to evaluate the effectiveness of dietary supplementation with purslane stems and young leaves and to determine the optimal dose to enhance soft-shell crab growth and molting. The study used a completely randomized design (CRD) with four treatments and three replicates, namely P0 (yellowstripe scad without purslane), P60 (yellowstripe scad + 60 g kg-1 purslane), P70 (yellowstripe scad + 70 g kg-1 purslane), and P80 (yellowstripe scad + 80 g kg-1 purslane). The results showed that purslane supplementation significantly increased molting and improved growth performance (P < 0.05). Treatment P70 yielded the highest molting percentage of 76.6% and growth rate of 1.3 g day⁻¹. Meanwhile, the control treatment (P0) only achieved a molting percentage of 36.6% and a growth rate of 1.07 g day⁻¹. These findings indicate that purslane has a potential as a natural feed additive to enhance molting and growth performance in soft-shell crab culture. The dose of 70 g kg-1 feed can be recommended to achieve the best molting response of soft-shell crab reared in a recirculating aquaculture system using the apartment box. Kendala utama dalam budidaya kepiting soka (Scylla serrata) adalah proses molting yang tidak serempak dan frekuensinya yang rendah, sehingga menurunkan efisiensi produksi. Penelitian sebelumnya menunjukkan bahwa suplementasi krokot (Portulaca oleracea) dapat meningkatkan molting dan kinerja produksi kepiting soka yang dibudidayakan dalam sistem kotak apartemen berbasis resirkulasi; namun, evaluasi pada dosis yang lebih tinggi masih terbatas. Penelitian ini bertujuan untuk mengevaluasi efektivitas suplementasi batang dan daun muda tanaman krokot dalam pakan serta menentukan dosis optimal untuk meningkatkan pertumbuhan dan molting kepiting soka. Penelitian ini menggunakan rancangan acak lengkap (RAL) dengan empat perlakuan dan tiga ulangan, yaitu P0 (ikan selar tanpa penambahan krokot), P60 (pakan ikan selar + 60 g kg-1 krokot), P70 (pakan ikan selar + 70 g kg-1 krokot), dan P80 (pakan ikan selar + 80 g kg-1 krokot). Hasil penelitian menunjukkan bahwa suplementasi krokot secara signifikan meningkatkan molting dan kinerja pertumbuhan (P < 0,05). Perlakuan P70 menghasilkan persentase molting tertinggi sebesar 76,6%, dan laju pertumbuhan 1,3 g hari-1. Sementara itu, perlakuan kontrol (P0) hanya mencapai persentase molting sebesar 36,6% dan laju pertumbuhan sebesar 1,07 g. hari-1. Hasil ini menunjukkan bahwa tanaman krokot berpotensi sebagai bahan tambahan pakan alami untuk meningkatkan molting dan pertumbuhan pada budidaya kepiting soka. Dosis 70 g kg-1 pakan dapat direkomendasikan untuk menghasilkan respons molting terbaik pada kepiting soka yang dipelihara dalam sistem resirkulasi dengan metode kotak apartemen.